Remote Work Aided by Conversational Agents - Qiu, Sihang; Gadiraju, Ujwal; Bozzon, Alessandro (2020)
ABSTRACT Due to the coronavirus pandemic, remote work from home has rapidly become a necessity around the world, drastically changing the potential landscape for the future of work. Over the last couple of decades, microtask crowdsourcing has emerged as a viable means of carrying out remote online work to earn one’s living — an alternative to traditional work for a large number of people. In the aftermath of the pandemic, there is likely to be an increase in people who need to work from home due to a variety of reasons, ranging from safety and well-being to massive layoffs. However, current crowdsourcing platforms and marketplaces are not adequately optimized for worker satisfaction or engagement. There is a need for a new means of interaction that can engage the workers, support their cognitive needs, cater to their well-being – all without compromising on the quality of work being produced. Drawing inspiration from prior studies which have shown that conversational systems can improve user experiences, we investigate the feasibility of microtask crowdsourcing aided by conversational agents. Findings based on our recent research in conversational microtasking, have important implications on improving both, the subjective mental condition and objective output quality of workers. We believe that conversational agents have an important role to play in shaping how remote work can be carried out in the imminent future. Keywords Conversational Agent, Microtask, Crowdsourcing, Quality, User Engagement, Remote Work. ABOUT THE AUTHOR/S Sihang Qiu Delft University of Technology Delft s.qiu-1@tudelft.nl Sihang Qiu is a PhD candidate at the Web Information Systems group of the Faculty of Engineering, Mathematics and Computer Science (EEMCS/EWI), Delft University of Technology. His PhD topic focuses on Conversational Interfaces for Crowdsourcing. He also has broad interests in Mobile Crowdsensing and Human-Computer Interaction. Ujwal Gadiraju Delft University of Technology Delft u.k.gadiraju@tudelft.nl Alessandro Bozzon Delft University of Technology Delft a.bozzon@tudelft.nl New Future of Work 2020, August 3–5, 2020 © 2020 Copyright held by the owner/author(s).